The relationship between social media and employees’ performance at Pejabat Pendidikan Daerah Jerantut, Pahang / Noor Ata Sha Amira Morat - Morat, Noor Ata Sha Amira (2017)
The rise of social media is rapidly changing as well as how organization operated and communicated. This study aims to investigate the relationship between social media and employees’ performance at Pejabat Pendidikan Daerah Jerantut. The independent variable is focus on three types of social media which are Facebook, Twitter and Instagram while dependent variable is employees’ performance. The overall objectives of the study were to study the most preferred type of social media among employees and to identify the relationship between social media and employees’ performance at Pejabat Pendidikan Daerah Jerantut. The problem statement of this research is most employees using social media during work hour have effect their productivity and performance. This study was conducted by using 100 respondents that were selected from all employees that has used social media at workplace. In order to collect the primary data, the distribution of questionnaires was used. Firstly, the researcher conducted the pilot test at Petronas Gas Berhad Kerteh that involved 30 respondents. As for actual place which is at Pejabat Pendidikan Daerah Jerantut, the researcher distributed the questionnaires to 103 respondents that were decided by using stratified random sampling technique and Krijcie and Morgan’s table (1970) from the total of 145 employees. However, 100 questionnaires were fully completed and 3 of them are unreturnable. The obtained data from the questionnaires were analyzed using IBM Statistical Package for the Social Science (SPSS) software version 20. The finding of the study was presented by the Cronbach’s Alpha value for all variables during pilot test and actual test for reliability analysis. For the normality test, the result shows that data for both independent and dependent variable are normal. This study also shows the finding based on research objective. Research objective I was answered by using the highest mean to identify the most preferred types of social media among employees at Pejabat Pendidikan Daerah Jerantut and it shows that Instagam has the highest mean among others variable. Meanwhile for the Research objective II, there was strong and significant relationship between social media and employee’s performance with Facebook hold the highest correlation. Based on the results obtained, the researcher suggest some recommendations to serve as guidelines for future plan in improving the employees’ performance at Pejabat Pendidikan Daerah Jerantut